Resistive Loss in PV Array Configurations : Impact of Cable Length and Cross-Section on Power Performance using MATLAB/Simulink Analysis - Lawrence Sii, Ying Ting; Then, Yi Lung; Simon Sie, Liung Ngu; Abadi, Chanik@Azhar (2025)
The performance of photovoltaic (PV) arrays is strongly affected by resistive losses in interconnecting cables, yet the combined influence of cable size and array configuration is often overlooked in system design. This study examines how cable length (5 m and 20 m) and cross-sectional area (2.5, 4, 6, and 10 mm²) influence the output of four different 4x4 PV array topologies: Series, Parallel, Bridge-Link, and Honeycomb. A MATLAB Simulink model is developed to simulate resistive losses under various cable conditions, with array performance assessed at peak power output. Results show that longer cable runs and smaller cross-sectional areas increase resistance and reduce available power. The impact is especially large in the Series configuration, where output remains near 1,136 W regardless of CSA, even as other topologies exceed 3,300 W under the same conditions. The Honeycomb configuration consistently delivers the highest output across all cable lengths and sizes, closely followed by Bridge-Link and Parallel. At 20 m length, increasing CSA from 2.5 mm² to 10 mm² improves power by up to 9.4% in Honeycomb, while offering negligible benefit in Series. At 5 m length, the gap between topologies narrows, but Honeycomb and Bridge-Link still provide slightly better performance. The results emphasize that array layout plays a larger role than cable thickness in minimizing resistive losses, particularly in longer installations. Using optimized configurations such as Honeycomb or Bridge-Link with moderate cable sizes (e.g., 6 mm²) achieves high efficiency without unnecessary material cost. These insights support design strategies that reduce energy losses and copper usage in medium to large-scale PV systems.